UPLC fingerprinting combined with quantitative analysis of multicomponents by a single marker for quality evaluation of YiQing granules - YangHong Li; Bao Yu; Bao Yu; Wei Zhao; Xiyu Pu; Xue Zhong; Xingbao Tao; Yunhong Wang; Weiguo Cao; Dan Zhang; Dan Zhang (Frontiers in Chemistry)
Research backgroundYiQing granules (YQGs) are a patented drug commonly used in clinics in China. However, the quality control index of this preparation is relatively limited, which does not effectively ensure the quality of the product. Thus, a comprehensive quality evaluation of YQGs is lacking.ObjectiveThe aim of this study was to establish a method for quantitative and qualitative analysis of YQGs based on ultra-high performance liquid chromatography-photodiode array detector (UPLC-PAD) fingerprint combined with quantitative analysis of multicomponents by a single marker (QAMS).MethodsWe established and verified the comprehensive evaluation method that UPLC fingerprint combined with QAMS and stoichiometric method, to assess the overall quality of YQGs produced by different manufacturers. Berberine was selected as an internal reference, and the relative correction factors of coptisine, epiberberine, baicalin, berberine, palmatine, wogonoside, baicalein, wogonin, aloe-emodin, rhein, emodin, and chrysophanol were established.Study resultsResults showed that the experimental time of the fingerprint was significantly reduced to approximately 0.5 h using the UPLC–PAD method. A total of 32 common peaks with similarity greater than 0.9 were identified. The accuracy of QAMS was compared with the external standard method, with no significant difference between the two methods.ConclusionThe UPLC fingerprint combined with QAMS method established in this study is feasible and reliable; it can be used for the comprehensive quality evaluation of YQGs and can provide a reference for the quality evaluation of other traditional Chinese medicine preparations.